Pour une généalogie critique de la Francophonie - Premat, Christophe (Stockholm Studies in Romance Languages, 2018)
"Christophe Premat is a senior lecturer in cultural studies in the Department of Romance Studies and Classics at Stockholm University and Co-Editor-In-Chief for the Nordic Journal of Francophone Studies, https://franorfon.org. The book studies the genesis of the institutions of the Francophonie at the time of independence of African countries in the sixties. Based on geopolitical analysis and postcolonial theories, the author reassesses the position of France which officially distanced itself from this multilateral organization. France controlled more and more the organization in the 1980s when the organization increased its political expression on international issues. By confronting the spirit of the structures with the actors of the Francophonie, the work reflects on the challenges and the difficulty to define the specific fields of action of this organization. Furthermore, the book proposes a critical analysis of the francophone discourse based on the ideology that makes the French language an instrument containing values and norms."